The Influence of Work Discipline, Workload and Work Motivation on Employee Productivity PT. BPR Kerta Raharja KPO - Salsyyah, Diana Bayi; Sarah, Siti (Dinasti International Journal of Management Science, 2025)
The goal of this studies is to look at the person and collective influences of workload, paintings discipline, and work pressure on worker overall performance at PT BPR Kerta Raharja KPO. people have been interviewed and given surveys a good way to collect data. members were selected thru non-probability sampling for the observe. the usage of the SPSS software, facts changed into analyzed the use of a couple of linear regression. The observe discovered that the productiveness of PT BPR Kerta Raharja KPO people changed into significantly impacted by way of paintings motivation in a terrible manner and by using workload and work field in a high quality way. The performance of PT BPR Kerta Raharja KPO employees turned into favorably and extensively impacted by work subject, workload, and motivation whilst evaluated collectively. additionally, the findings validated that eighty two. nine% of the have an effect on on how properly PT BPR Kerta Raharja KPO employees carry out their duties can be attributed to workload, work subject, and paintings motivation, with the remaining 18. 1% being encouraged through additional factors not explored in this examine.